Reducing Misconceptions on the Concept of Vibration and Waves with CCM CCA to Improve Creative Thinking Skills - Muh. Makhrus; Susilawati Susilawati; Wahyudi Wahyudi; Hikmawati Hikmawati; Hairunnisyah Sahidu (Postgraduate, University of Mataram, 2023)
Education in the 21st century currently requires students to improve higher-order thinking skills (Higher Other Thinking Skills), one of which is creative thinking skills. A good conceptual understanding will support higher-order thinking skills, especially creative thinking skills. This study aims to reduce students' misconceptions about the concept of vibration and waves with CCM CCA and to improve students' creative thinking skills. Subjects in this case amounted to 29 students. Students' creative thinking skills are measured from the results of tests carried out 2 times, namely in the form of an initial test (pretest) and a final test (posttest) which refer to indicators of students' creative thinking skills. Items in both tests are equipped with response answers (reasons for answering questions) and all test items are equipped with several answer choices that indicate the level of certainty of answer responses. The method in this research is descriptive quantitative. The results of the study show that the CCM CCA learning model can reduce students' misconceptions about vibration and wave concepts and improve their creative thinking skills.